DNA Diagnosis of Thalassemia From Ancient Italian Skeletons - Yang, Dongya (My University, 1997)
This thesis reports an attempt to extract DNA from the skeletal remains of five young children who died approximately 1,900 years ago and who were recovered from an Italian archaeological site, Isola Sacra. These skeletons have been tentatively diagnosed as thalassemics based on morphological observations, but alternative diagnoses are also possible. DNA diagnosis was used to attempt to identify thalassemia mutations from the human globin genes extracted from these skeletons.
Successful extraction of the human globin genes is largely dependent on two factors: retrieving sufficient amounts of ancient DNA without PCR (Polymerase Chain Reaction) inhibitors, and no contamination from modern DNA. To improve the chances of success, a more efficient and rapid method of extracting DNA from ancient skeletons was developed using a silica-based spin column technique to maximize the yield of amplifiable DNA from ancient skeletons and minimize the risk of the contamination with modern DNA. In a single step, the DNA is concentrated and separated from non-DNA substances that could inhibit PCR. This sufficiently removed PCR inhibitors but without an increased risk of contamination. A comparison test proved that this new approach is superior to current commonly used methods.
Upon application of the new method, the evidence suggests that ancient human p-globin genes were extracted from three of the five individuals from Isola Sacra. DNA diagnosis for two of the most common Italian thalassemia mutations, IVS 1-11 a and codon 39 (more than 50% of current Italian thalassemia mutations),revealed that these three individuals did not have these two mutations. However, the present results cannot totally exclude the possibility of thalassemia from these specimens since five other untested mutations might occur in these specimens.
Precautions were taken to minimize the risk of contamination. Contamination was also monitored by mtDNA analysis of each individual. No systemic contamination took place in this study but a sporadic contamination was identified with one specimen. The further analysis clearly indicated that the contamination came from the author.
This thesis has shown that DNA diagnosis of diseases from ancient remains can be a new, powerful approach to the study of health and disease in past human populations. Technical improvements and revised research strategies are expected to advance DNA diagnoses of ancient diseases.
[Missing page v]
Keywords: Biological and Physical Anthropology; Biological and Physical Anthropology